Taṭwīr al-Waṣīlah al- Ta‘līmīyah “Ludo” li-Māddat al-Lughah al-‘Arabīyah fī Madrasat al-Azhar al-Thānawīyah al-Islāmīyah, Kelapa Gading, Jakarta - Ahmad Marzuq; Khifni Nurani (Al-Ma‘rifah, 2019)
This study aimed to develop the Ludo game as a media to improve students learning motivation and help students in grade XI Al-Azhar Islamic High School Kelapa Gading doing the vocabularies task; to know the feasibility of learning media Ludo based on research from material experts and media experts, and to find out the assessment of students towards Ludo’s learning media. The results of the study were obtained through five steps in producing Ludo’s learning media: (1) Analyzing students’ needs in learning. It was considered as important for the product to be developed; (2) Designing the product which is game board design and question cards containing Arabic images and vocabulary; (3) Development; the process of evaluating product design was conducted by giving an assessment. Product assessment was carried out by material experts and media experts; (4) Implementation; testing the feasibility of learning media Ludo with 15 field trial students. The trial was conducted to determine the effectiveness of the product; (5) Evaluation; the product based on the results of the questionnaire were given to material experts, media experts, and Al-Azhar Islamic High School Kelapa Gading students. The level of feasibility of Ludo learning media based on assessment: (1) The material expert showed the average percentage is 96% (very decent); (2) media expert showed the average percentage is 94% (Very decent). The scoring of the students in the experiment showed that the average percentage is 89% (very decent). Therefore, Ludo is suitable to be used as a learning media.